2021
DOI: 10.1038/s41598-021-81295-4
|View full text |Cite
|
Sign up to set email alerts
|

The nitrogen topdressing mode of indica-japonica and indica hybrid rice are different after side-deep fertilization with machine transplanting

Abstract: Determination of the optimal fertilization method is crucial to maximize nitrogen use efficiency and yield of different rice cultivars. Side-deep fertilization with controlled-release nitrogen, in conjunction with machine transplanting and subsequent topdressing, was applied to Indica–japonica hybrid rice ‘Yongyou1540’ (YY1540) and indica hybrid rice ‘Tianyouhuazhan’ (TYHZ). Four nitrogen treatments were applied in 2018 and 2019: traditional nitrogen application with quick-release nitrogen (T1), single-dose de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…However, the results of Wang et al [27] concern long-term (14 years) tillage effects on soil and rice. Long-term NT or RT could increase soil compactness, restrict air from entering deep soil, accumulate reducing substances in deep soil, and limit the growth of rice roots [28]. Das et al [11] reported that short-term (4 years) NT increased soil organic carbon, microbial biological carbon, and dehydrogenase activity, and provided superior conditions for root growth.…”
Section: Effects Of Tillage and Fertilization Treatments On Root Func...mentioning
confidence: 99%
“…However, the results of Wang et al [27] concern long-term (14 years) tillage effects on soil and rice. Long-term NT or RT could increase soil compactness, restrict air from entering deep soil, accumulate reducing substances in deep soil, and limit the growth of rice roots [28]. Das et al [11] reported that short-term (4 years) NT increased soil organic carbon, microbial biological carbon, and dehydrogenase activity, and provided superior conditions for root growth.…”
Section: Effects Of Tillage and Fertilization Treatments On Root Func...mentioning
confidence: 99%
“…Previous studies reported that appropriately increasing the panicle N application rate reduced the number of ineffective tillers and increased the percentage of productive tillers, leading to an increase in the dry matter weight per stem [32][33][34]. The canopy transmittance and root activity were improved by applying more N in the late stage of rice [17,35].…”
Section: Reasonable N Regime In the Main Crop Improved The Growth And...mentioning
confidence: 99%
“…If fast-acting fertilizer is used for side-deep fertilization, the nitrogen concentration in the soil layer will be reduced 30 days after rice transplanting, avoiding lodging caused by overgrowth, fully reducing ineffective rice tillers, and promoting early rice development (Zhu et al ., 2019 b ). If side-deep fertilization is done with a controlled-release fertilizer, nutrients can be released slowly over the entire growth period, and can release nutrients at a suitable rate for the rice plant's requirements (Xiao-Dan et al ., 2021). But there are also studies that point out (Lyu et al ., 2021), since a controlled-release fertilizer has a slow release of nutrients in the early stage of rice growth, it is not conducive to rice tillering.…”
Section: Impact Of Side-deep Fertilization On Rice and Soilmentioning
confidence: 99%
“…Therefore, the fertilizer requires a stable composition, good surface compression resistance, uniform particle size distribution and stable water absorption characteristics (Massoudi, 2001;Linquist et al, 2012). Wang et al (2020) analyzed more than ten mainstream granular fertilizers, including slow-and controlled-release fertilizers, special rice fertilizers, compound fertilizers, blended fertilizers and controlled-release urea, and finding that their average particle size was 3-4 mm. The fertilizer with the best stability was 'Heart to Heart' controlled-release urea, which basically does not absorb water.…”
Section: Fertilizer Types and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation